2014
DOI: 10.1002/j.1532-2149.2014.484.x
|View full text |Cite
|
Sign up to set email alerts
|

Topical high‐concentration menthol: Reproducibility of a human surrogate pain model

Abstract: For an observation period of 1 week, the signs of cold and mechanical hyperalgesia were reproducible with a highly significant correlation of about r = 0.8 and good agreement except for the area size of mechanical pin-prick hyperalgesia. These results demonstrate that the topical menthol pain model is suitable for pharmacological interventions repeated within an observation period of 1 week.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 35 publications
0
23
0
Order By: Relevance
“…In the present study we sought to evaluate the analgesic, anti-hyperalgesic and antiinflammatory effect of L-menthol to CA-induced sensory and vasomotor symptomatology, and as such did not include a condition with L-menthol alone, which is well known to induce prolonged cold hyperalgesia, spontaneous pain and primary and secondary hyperalgesia. 3,8,34,43,50,62,63 Topical application of 10% CA provoked mild pain, primary and secondary mechanical hyperalgesia, heat and cold hyperalgesia and substantial primary and secondary neurogenic inflammation. Notably, 3 subjects were considerably below the averagely reported pain peak values and scored ≤ 1 (0.80 ± 0.05) on the VAS versus 3.87 ± 0.46, for the remaining 11 subjects.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study we sought to evaluate the analgesic, anti-hyperalgesic and antiinflammatory effect of L-menthol to CA-induced sensory and vasomotor symptomatology, and as such did not include a condition with L-menthol alone, which is well known to induce prolonged cold hyperalgesia, spontaneous pain and primary and secondary hyperalgesia. 3,8,34,43,50,62,63 Topical application of 10% CA provoked mild pain, primary and secondary mechanical hyperalgesia, heat and cold hyperalgesia and substantial primary and secondary neurogenic inflammation. Notably, 3 subjects were considerably below the averagely reported pain peak values and scored ≤ 1 (0.80 ± 0.05) on the VAS versus 3.87 ± 0.46, for the remaining 11 subjects.…”
Section: Discussionmentioning
confidence: 99%
“…22,48 TRPA1 is suspected to be involved in noxious cold transmission (,15˚C) and is expressed on C-and Ad-fibers. 44 It is generally agreed 8,23,31,47 that application of L-menthol increases the average temperature of the cold pain threshold (CPT), reduces mechanical pain threshold, and increases mechanical pain sensitivity. However, there is still a lower consensus on the development of secondary mechanical hyperalgesia, its stability and the duration of its existence.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, from the statistical review of effects it can be concluded from the distributions of values at premodel baseline and pre-tapentadol baseline that, in this study, a high variability in QST values could have influenced the outcome measures. For example, this might be explained by the fact that subjects were tested in the ratio 4 subjects: 2 investigators in one room and not in the ratio 1:1 previously described in evoked pain model studies [14,15] . This leads to the question of sample size and assay sensitivity that might have been too low in this complex study although common methods and sample sizes were used.…”
Section: Methodological Limitationsmentioning
confidence: 99%
“…The topical menthol model demonstrated robust induction of cold and mechanical hyperalgesia with a high grade of reproducibility [14,15] . Similar data were shown for the capsaicin injection and heat-capsaicin model only, not for the topical application model used in this study.…”
Section: Methodological Limitationsmentioning
confidence: 99%
See 1 more Smart Citation